Human Health Risk Assessments and Characterization of Nanomaterials: Are We Ready for the Next (Active) Generations?. Issue 7 (28th April 2021) - Krystek, Petra; Shandilya, Neeraj; Fransman, Wouter
Abstract: Driven by the concept of the 'four generations of nanomaterials', the current state of the knowledge on risk assessment of future generation is explored for active nanomaterials. Through case studies, we identify challenges and evaluate the preparedness of characterization methods, available risk assessment modeling tools, and analytical instrumentation for such future generation active nanomaterials with dynamic hybrid structures of biotic–abiotic and organic–inorganic combinations. Currently available risk assessment tools and analytical instrumentation were found to be lacking the risk preparedness and characterization readiness for active nanomaterials, respectively. Potential future developments in risk assessment modeling tools and analytical techniques can be based upon this work which shall ensure long-term safety of the next generation of nanomaterials.